Study of praziquantel phytoremediation and transformation and its removal in constructed wetland - Marsik, P; Podlipna, R; Vanek, T (Journal of hazardous materials, 2017)
Accumulation and/or degradation of Praziquantel (PZQ) in plants were determined using Phragmites australis, both suspension cultures and in vitro cultivated plants. In case of initial PZQ concentration 20mgL-1, 90% was removed from liquid media within 21days. The accumulated PZQ was partly metabolized, twenty one compounds being identified, products of both Phase I and II of detoxification metabolism. Laboratory results were confirmed in real scale using the constructed wetland (CW), where PZQ (500mg in total) was completely removed until the first purification pond. This result offers a promising possibility to use CW for PZQ removal from agricultural as well as domestic waste-waters.
Keywords: rostliny; mokřady; praziquantel; Phragmites; Environmental Restoration and Remediation; Veterinary Drugs; Biodegradation, Environmental; biodegradace; agrochemikálie; Poaceae; Plants; Metabolisms; Waste Disposal, Fluid; odpad tekutý - odstraňování; Wetlands; Praziquantel; Anthelmintics; Pharmaceuticals; veterinární léky; Agrochemicals; lipnicovité; regenerace a remediace životního prostředí; Waste waters